2011
DOI: 10.1016/j.molcel.2011.04.004
|View full text |Cite
|
Sign up to set email alerts
|

L3MBTL2 Protein Acts in Concert with PcG Protein-Mediated Monoubiquitination of H2A to Establish a Repressive Chromatin Structure

Abstract: SUMMARY We have identified human MBT domain-containing protein L3MBTL2 as an integral component of a protein complex that we termed Polycomb Repressive Complex 1 (PRC1)-like 4 (PRC1L4) given the co-presence of PcG proteins RING1, RING2 and PCGF6/MBLR. PRC1L4 also contained E2F6 and CBX3/ HPlγ known to function in transcriptional repression. PRCIL4-mediated repression necessitated L3MBTL2 that compacted chromatin in a histone modification-independent manner. Genome-wide location analyses identified several hund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
179
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(194 citation statements)
references
References 51 publications
(71 reference statements)
12
179
2
1
Order By: Relevance
“…This has been clearly demonstrated for the case of L3MBTL2, which does not seem to stimulate RING1A/RING1B activity in vitro, and was therefore suggested to act as a recruiter exclusively. 40 Because L3MBTL2 has its own biochemical activities by which it can compact chromatin in vitro 40 , recruitment of L3MBTL2 and PRC1 could facilitate local chromatin compaction in a histone modification independent manner. Indeed, our observations that both L3MBTL2 and L3MBTL1 are expressed throughout pre-implantation development could provide more versatile actions of polycomb-related function at specific genome locations at a given developmental time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been clearly demonstrated for the case of L3MBTL2, which does not seem to stimulate RING1A/RING1B activity in vitro, and was therefore suggested to act as a recruiter exclusively. 40 Because L3MBTL2 has its own biochemical activities by which it can compact chromatin in vitro 40 , recruitment of L3MBTL2 and PRC1 could facilitate local chromatin compaction in a histone modification independent manner. Indeed, our observations that both L3MBTL2 and L3MBTL1 are expressed throughout pre-implantation development could provide more versatile actions of polycomb-related function at specific genome locations at a given developmental time.…”
Section: Discussionmentioning
confidence: 99%
“…RYBP is expressed in pre-implantation mouse embryos PRC1 complexes can mediate H2AK119ub independently of H3K27me3 and PRC2 proteins. 22,40 The dynamics and localization pattern of H3K27me3 in conjunction with that of PRC2 components have been well studied in the mouse embryo. 25,27,28 Therefore, having established that H2AK119ub was present in preimplantation development, we wondered whether non-canonical PRC1 complexes contribute also to H2AK119 ubiquitylation.…”
Section: H2ak119 Monoubiquitination Is Dynamic During Preimplantationmentioning
confidence: 99%
“…In this review, we will discuss these broader issues by using 2 complex families as examples: MBT domain proteins and complexes containing CoREST proteins [14][15][16][17][18][19] (Table 1). When MBT and CoREST complexes were originally isolated they were viewed as belonging to distinct families that did not share common subunits (Fig.…”
Section: Merging Protein Complex Familiesmentioning
confidence: 99%
“…Incubation of the MBT domains of L3MBTL1 or of full-length L3MBTL2 with oligo-nucleosomal arrays results in chromatin compaction in vitro. 14,15 Moreover, expression of recombinant full-length SFMBT1 or its MBT domains in cell lines reduces chromatin accessibility to nuclease digestion. 23 As we will detail below, MBT domain proteins are found in several multisubunit protein complexes (see Table 1 for a list of MBT and CoREST complexes discussed in this review).…”
Section: -23mentioning
confidence: 99%
“…In a series of elegant experiments, LaFave et al (92) observed that BAP1 mutations, which typically result in loss of protein expression, increased EZH2 as well as SUZ12 expression in MPM cells. Up-regulation of EZH2 in BAP1 mutant cells was associated with reduced levels of H4K2Me1, as well as decreased occupancy of L3MBTL2 (an atypical polycomb protein which recognizes this repressive histone mark) within the EZH2 promoter (96,97). Additional experiments demonstrated that BAP1 deubiquitinates and thereby stabilizes and co-localizes with L3MBTL2 within the EZH2 promoter.…”
Section: Polycomb Mediated Gene Silencingmentioning
confidence: 86%